Nuclear elongation during spermiogenesis depends on physical linkage of nuclear pore complexes to bundled microtubules by Drosophila Mst27D. - Li, P.; Messina, G.; Lehner, C.F. (PLoS Genetics, 2023)
Spermatozoa in animal species are usually highly elongated cells with a long motile tail attached to a head that contains the haploid genome in a compact and often elongated nucleus. In Drosophila melanogaster, the nucleus is compacted two hundred-fold in volume during spermiogenesis and re-modeled into a needle that is thirty-fold longer than its diameter. Nuclear elongation is preceded by a striking relocalization of nuclear pore complexes (NPCs). While NPCs are initially located throughout the nuclear envelope (NE) around the spherical nucleus of early round spermatids, they are later confined to one hemisphere. In the cytoplasm adjacent to this NPC-containing NE, the so-called dense complex with a strong bundle of microtubules is assembled. While this conspicuous proximity argued for functional significance of NPC-NE and microtubule bundle, experimental confirmation of their contributions to nuclear elongation has not yet been reported. Our functional characterization of the spermatid specific Mst27D protein now resolves this deficit. We demonstrate that Mst27D establishes physical linkage between NPC-NE and dense complex. The C-terminal region of Mst27D binds to the nuclear pore protein Nup358. The N-terminal CH domain of Mst27D, which is similar to that of EB1 family proteins, binds to microtubules. At high expression levels, Mst27D promotes bundling of microtubules in cultured cells. Microscopic analyses indicated co-localization of Mst27D with Nup358 and with the microtubule bundles of the dense complex. Time-lapse imaging revealed that nuclear elongation is accompanied by a progressive bundling of microtubules into a single elongated bundle. In Mst27D null mutants, this bundling process does not occur and nuclear elongation is abnormal. Thus, we propose that Mst27D permits normal nuclear elongation by promoting the attachment of the NPC-NE to the microtubules of the dense complex, as well as the progressive bundling of these microtubules.